THE EFFECT OF CREDIT POLICIES ON LOAN PERFORMANCE, A CASE STUDY OF PRIDE MICROFINANCE MUKONO BRANCH - Shablinah Nazziwa (Uganda Christian University, 2025)
The study investigated the effect of credit policies on loan performance; a case of pride microfinance bank Mukono branch. The study was guided by the following objectives;To examine the effect credit terms on loan performance at pride microfinance Mukono branch , To establish the effect of Credit appraisal on loan performance the at pride microfinance Mukono branch and To assess the effect of Credit monitoring on loan performance the at pride microfinance Mukono branch. The study employed descriptive research design to comprehensively examine the effectiveness of credit policies in influencing loan performance at pride microfinance Mukono branch. The study as well adopted a quantitative approach. The study established that; the composite mean for credit terms was 3.61 (SD = 0.65), indicating moderate agreement that credit terms enhance loan performance, though high interest rates limit their effectiveness. The composite mean for credit appraisal was 3.83 (SD = 0.60), suggest strong agreement that appraisal processes enhance loan performance. The composite mean for credit monitoring was 4.06 (SD = 0.59), the highest among the three policy components, indicating that monitoring is perceived as the most effective in reducing NPLs and enhancing loan performance. The study concluded that credit policies comprising credit terms, appraisal, and monitoring positively influence loan performance at Pride Microfinance Mukono Branch. Monitoring has the strongest impact, followed by appraisal, while credit terms are less effective due to high interest rates. These findings validate the conceptual framework and address the problem statement, which highlighted the 17% NPL rate in 2020 as a threat to Pride Microfinance’s financial stability.
Undergraduate thesis